Long-Range OFDR-Based Distributed Vibration Optical Fiber Sensor by Multicharacteristics of Rayleigh Scattering - Zhenyang Ding; Di Yang; Kun Liu; Junfeng Jiang; Yang Du; Bingkun Li; Minghao Shang; Tiegen Liu (IEEE Photonics Journal, 2017)
We present a long-range optical frequency domain reflectometry (OFDR) based distributed vibration optical fiber sensor (DVOFS) by multicharacteristics of Rayleigh scattering. Comparing with utilizing a single characteristic of Rayleigh scattering, by using multicharacteristics of Rayleigh scattering, two or more simultaneous vibration events in a long sensing range can be detected and located in DVOFS. In a single-ended OFDR-based DVOFS without any optical amplification, we can discriminate two simultaneous vibration events by two different characteristics. One is the local Rayleigh scattering spectra shifts for locating the first vibration event. The other is the “V” shape in Rayleigh scattering signals in the spatial domain for locating the second vibration event. The sensing range of this DVOFS is 92 km and the spatial resolution of locating vibration events is 13 m.